Maxim Violation in “Dilbert” Comic Strips - Alfonsa Vina Kanasya; Barli Bram (Hasanuddin University, 2022)
This research investigates the conversations in the “Dilbert” comic written by Scott Adams. The data came from the dialogues in the comic “Dilbert.” They were analyzed using Gricean Maxims of Conversations. This qualitative study used content analysis as the data of this research is text. This research aimed to analyze the maxims that were violated in this comic to create humor and the reason why the characters were violating the maxims during conversations. Fifteen comic strips from the website dilbert.com were chosen and analyzed. The results show that the characters mostly violate maxims of relevance since they need to come up with an excuse for the given questions or avoid accusation. They also violate the maxim of quality as they sometimes lie too in order to get out of the situation or accusation.